Peran Orang Tua Dan Relevansinya Dengan Pembelajaran Pendidikan Agama Islam Berbasis Teknologi Informasi - Zuliyanti, Roisyah; Amirudin, noor; Ladamay, Man Arfa' (STIT Muhammadiyah Paciran, 2021)
The purpose of Islamic Religious Education is to form human beings or noble character. However, this goal has not been realized, because the nation's morale is getting worse. So there needs to be a substantial effort from parents in the formation of morals. Parents are the main role models, children will imitate what is done by parents and parents as role models. This study aims to determine the role of parents in Ani Christina's School Becoming Parents book and its relevance to information technology-based Islamic religious education learning. The type of research used is descriptive qualitative research with a library research approach. Collecting data in the form of interviews and documentation, namely by collecting data from several sources and sources of literature related to the research conducted. The data analysis used content analysis method and interpretation method. The results of the study indicate that the role of parents in Ani Christina's book School Being a Parent is that parents are role models in the educational process, everything parents do and what happens in the family is much more significant for children than outside influences. Furthermore, there is a relevance between the role of parents and the information technology-based Islamic Religious Education learning model. Its relevance lies in the characteristics of PAI subjects and their learning approaches.